2012
DOI: 10.1080/01635581.2012.707277
|View full text |Cite
|
Sign up to set email alerts
|

Fruit, Vegetable, and Animal Food Intake and Breast Cancer Risk by Hormone Receptor Status

Abstract: Background The effects of diet on breast cancer are controversial and whether the effects vary with hormone receptor status has not been well investigated. This study evaluated the associations of dietary factors with risk for breast cancer overall and by hormone receptor status of tumors among Chinese women. Methods The Shanghai Breast Cancer Study, a large, population-based, case-control study, enrolled 3,443 cases and 3,474 controls in 1996–1998 (phase I) and 2002–2004 (phase II); 2,676 cases had ER and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 51 publications
8
51
0
2
Order By: Relevance
“…Furthermore, the results of an American study suggest that a high supply of folic acid is associated with a decreased risk of female breast cancer [25]. This corresponds to Chinese observations according to which a frequent consumption of fruits and vegetables [26], and fermented dairy products [19], also being rich in folic acid, plays a role in the dietary prevention of female breast cancer. Noticeably, milk and its products are also characterized by low GI.…”
Section: H -High M -Moderate L -Low Level Of Self-efficacy (Gses)/omentioning
confidence: 84%
“…Furthermore, the results of an American study suggest that a high supply of folic acid is associated with a decreased risk of female breast cancer [25]. This corresponds to Chinese observations according to which a frequent consumption of fruits and vegetables [26], and fermented dairy products [19], also being rich in folic acid, plays a role in the dietary prevention of female breast cancer. Noticeably, milk and its products are also characterized by low GI.…”
Section: H -High M -Moderate L -Low Level Of Self-efficacy (Gses)/omentioning
confidence: 84%
“…Bao (2012) (12) Fig. 4 Forest plots of case-control (a) and cohort (b) studies on apple consumption (highest v. lowest category) and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…General characteristics of case-control and cohort studies are shown in Tables 1 and 2, respectively. Case-control studies were published between 1994 and 2014; three were conducted in Italy (13,19,22) , two each in Iran (10,15) , China (12,23) and Australia (14,29) , and one each in Poland (16) , Spain (11) , Czech Republic (17) , Brazil (18) , UK (20) , India (24) , Hawaii (25) , Mexico (26) , Sweden (27) and Uruguay (28) . One was a multinational study conducted in nine countries worldwide (Italy, Spain, Poland, Northern Ireland, India, Cuba, Canada, Australia and Sudan) (21) Cohort studies were published between 1998 and 2012; nine were conducted in the USA (30,31,(34)(35)(36)(37)39,40,45) and eight were conducted in Europe (32,33,38,(41)(42)(43)(44)46) .…”
Section: Literature Searchmentioning
confidence: 99%
“…In addition, Bao et al (2012) reported decrease in breast cancer risk among Chinese women for high intake of vegetables and citrus fruits.…”
Section: Discussionmentioning
confidence: 99%